Pavement mix design alternative use of waste product as filler material - Ho, Kui Hua. (Universiti Malaysia Sarawak (UNIMAS), 2010)
Due to the increasing number of vehicles and traffic volume, the performance on pavement design can be affected over a lifetime. Thus, modification on the pavement mixture is a way that can improve the performance of the bituminous pavement. Yearly, millions of tons of domestic wastes are produced and considerable percentages of these domestic wastes have desirable properties that can be considered suitable for a variety of sustainable application. Among these domestic wastes, chicken bones scientifically called Gallus gallus domesticus and blood cockle shells scientifically called Andara granosa were often thrown away after removing the flesh and mussels. Therefore, this study was conducted to investigate the effect of chicken bones and blood cockle shells as filler material in hot mix asphalt (HMA). Samples were prepared for wearing course of 14 mm nominal maximum aggregate size (AC14) with asphalt content ranging from 4% to 6.0% for both mixtures. Blood cockle shells and chicken bones were used to replace Ordinary Portland Cement (OPC) which is prepared as a control sample. Marshall Test was conducted on each sample to de ermine the stability, flow, density, voids in total mix (VTM), voids in mineral aggregate (VMA) and voids filled with asphalt (VF A) and was compared with lKR specification and control sample. The results showed modified HMA with blood cockle shells have high flow, stability and stiffness properties than the control sample. Hence, the blood cockle shells can be considered as an alternative filler material in the future for pavement design.